Performance Analysis of Public Transport in Khulna City: A Case Study on Journey to Work Purpose - Rabbi, Sanjida; Hossain, Kazi Salman; Rahman, Saima (Journal of Bangladesh Institute of Planners, 2015)
Public transport is one of the social facilities without which people’s life turned into stagnation and on the contrary, life becomes cozy by providing this facility. It is important to focus on the performance of existing public transport to ensure sustainable transportation system, rather importing more transport. The study finds performance of public transport in Khulna city based on the users, who use it at a regular basis for work purpose. Therefore, to find the performance, Customer Satisfaction Index (CSI) has been developed based on some service indicators. An Importance Performance Analysis (IPA) has been done to find the most important services indicators. Therefore, indicators like parking system and safety got more importance according to the method and also by the expert. CSI for Khulna city is measured 0.47 which lies in less satisfactory level. Users of Mahindra (0.47), CNG (0.49), and Auto Rickshaw (0.47) are less satisfied where Baby taxi (0.39) and bus services (0.37) cannot satisfy the users. Separate and powerful institutional authority for transit, public bus with better performance, policy (tax, tariff) for the parking system, online information system/ kiosk and union for the user can be initiated for the improvement of the performance. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 195-202